2006
DOI: 10.1007/s00467-006-0151-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of 735 children and adolescents with primary vesicoureteral reflux

Abstract: The purpose of this retrospective cohort study was to report the clinical course of children with primary vesicoureteral reflux (VUR). Between 1970 and 2004, 735 patients were diagnosed with VUR and were systematically followed in a single tertiary renal unit. Patients were followed up for a mean time of 76 months (6 months to 411 months). The events of interest were reflux resolution, renal damage, urinary tract infection (UTI), chronic kidney disease (CKD), and hypertension. Survival analysis was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 47 publications
6
61
2
2
Order By: Relevance
“…However, secondary VUR which is observed less commonly develops secondary to increased intra-bladder pressure due to anatomical, neurological or idiopathic causes (8). In the study performed by Silva et al (9), lower urinary system dysfunction was found in 114 of 671 patients (17%) with VUR. Vesicoureteral reflux is observed in approximately 20-50% of children with lower urinary system dysfunction (10).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, secondary VUR which is observed less commonly develops secondary to increased intra-bladder pressure due to anatomical, neurological or idiopathic causes (8). In the study performed by Silva et al (9), lower urinary system dysfunction was found in 114 of 671 patients (17%) with VUR. Vesicoureteral reflux is observed in approximately 20-50% of children with lower urinary system dysfunction (10).…”
Section: Discussionmentioning
confidence: 96%
“…Lower urinary system dysfunction not treated successfully has been reported to be one of the most important causes of recurring urinary tract infection (5-7). The relation of lower urinary system dysfunction and vesicouretheral reflux (VUR) has been studied in many studies (8)(9)(10)(11). Primary VUR is the most common form and is caused by proceeding of distal ureters in a short mucosal tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hypertension is strongly associated with renal damage (11) . In one study, 21% of the children with newly diagnosed hypertension had hypertension etiology showing renal scarring (12) .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of renal scars in hypertensive children is 21% (2). Longitudinal studies estimate 3% to 30% increment of the occurrence of hypertension after longtime follow up of patients with a history of parenchymal scarring secondary to vesicoureteral refl ux (VUR) and UTI during childhood (3)(4)(5). These studies are based on conventional blood pressure measurements.…”
Section: Introductionmentioning
confidence: 99%